Creating two self-assembly micro-environments to achieve supercrystals with dual structures using polyhedral nanoparticles - Yih Hong Lee (Nature Portfolio, 2018)
Crystals with multiple structures often perform special functions in nature, inspiring the creation of synthetic analogues. Here, the authors subject polyhedral nanoparticles to two self-assembly micro-environments to realize supercrystals with dual structures, in which the order of the surface layer differs from the bulk structure.